The Pedagogical and Psychological Importance of Personality-Oriented Education in the Educational Process - Himmatovich, Safarov Norboy (European Journal of Life Safety and Stability (2660-9630), 2022)
This article describes the pedagogical and psychological importance of personality-oriented education, its principles, function, objectives, its directions, views on the functions of the teacher in personality-oriented education.